2015
DOI: 10.1108/jpbm-10-2014-0722
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity endorsement, self-brand connection and consumer-based brand equity

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
2
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(188 citation statements)
references
References 53 publications
12
159
2
15
Order By: Relevance
“…This is due to the fact that for the individual consumer, such as Amanda, the celebrity's transgression poses a threat to their para-social relationship and to further 'consuming celebrity': forgiveness is a means to restoring and maintaining this relationship (Ho & Fung, 2011). As celebrities often represent aspirational reference groups (Escalas, 2004), any para-social relationship is likely to enhance the consumer's desired self (Dwivedi, Johnson, & McDonald, 2015). Therefore, protecting the relationship also means protecting oneself, as keeping the celebrity 'idolised' supports the survival of their own sense of identity and feelings of self-worth (Banister & Coker, 2014;Boon & Lomore, 2001).…”
Section: Consumer-related Driversmentioning
confidence: 99%
“…This is due to the fact that for the individual consumer, such as Amanda, the celebrity's transgression poses a threat to their para-social relationship and to further 'consuming celebrity': forgiveness is a means to restoring and maintaining this relationship (Ho & Fung, 2011). As celebrities often represent aspirational reference groups (Escalas, 2004), any para-social relationship is likely to enhance the consumer's desired self (Dwivedi, Johnson, & McDonald, 2015). Therefore, protecting the relationship also means protecting oneself, as keeping the celebrity 'idolised' supports the survival of their own sense of identity and feelings of self-worth (Banister & Coker, 2014;Boon & Lomore, 2001).…”
Section: Consumer-related Driversmentioning
confidence: 99%
“…Corroborating Bozic [50], Djafarova [24], Dwivedi [25] and Saldanha [17], the findings suggest that celebrity trustworthiness as having a positive influence on customer buying behaviour. This study defines trustworthiness as a consumer's perception towards the honesty, integrity and believability of a celebrity [16].…”
Section: Discussionmentioning
confidence: 65%
“…It is a celebrity endorser's perceived believability, honesty and integrity [16], whereas a celebrity's trustworthiness depends on the target audience's perceptions. Studies have found trustworthiness as having a positive influence on customer believe and highly opinionated recommendations from a highly trustworthy celebrity leads to an effective attitude change, and the vice versa [24,25,17]. Trustworthy celebrities are effective in the promotions of intangible product [20]; like insurance.…”
Section: Celebrity Attributesmentioning
confidence: 99%
“…A lealdade a marca pode ser a associadas a personagens ou atores. De acordo Dwivedi et al (2015) observou que a ligação das celebridades estár propício semelhante com a percepção da marca, a qualidade percebida, a associação da marca e a lealdade à marca para diversos produtos ou serviços. O valor de cada produto ou serviço, tanto monetario e quanto o valor agregado são diferenciais para fidelizar o cliente na hora da compra.…”
Section: Lealdade a Marcaunclassified